Isolation, identification and characterization of a novel antimicrobial peptide from Moringa oleifera seeds based on affinity adsorption. (1st January 2023) - Wang, Xuefeng; He, Li; Huang, Zhiyuan; Zhao, Qiong; Fan, Jiangping; Tian, Yang; Huang, Aixiang
Graphical abstract: Highlights: A novel antimicrobial peptide (MOp3) was isolated and identified from M. oleifera seeds. MOp3 exhibited potent antimicrobial activity and negligible hemolytic activity. MOp3 induced irreversible damage on cell membrane of Staphylococcus aureus. MOp3 interacted with DNA gyrase and dihydrofolate reductase of S. aureus. Abstract: This study aimed to characterize a novel antimicrobial peptide (AMP) obtained from Moringa oleifera seed protein hydrolysates. Cell membrane chromatography and live bacteria adsorption were combined into a single step to efficiently isolate the active fraction of the AMP. Five peptides were identified by LC-MS/MS, among which the MCNDCGA peptide (termed MOp3) showed the greatest inhibitory effect against Staphylococcus aureus [minimum inhibitory concentration (MIC): 2 mg/mL]. MOp3 was identified as a hydrophobic anionic AMP rich in β-sheet structures with negligible hemolytic activity at 2.0 × MIC. MOp3 had good tolerance to salt solutions at 5 % and pH range 6.0–8.0, but was sensitive to high temperatures (>100 °C) and acid protease. Microscopic observation further revealed that MOp3 induced irreversible damage onto the cell membrane of S. aureus and interacted with dihydrofolate reductase and DNA gyrase by hydrogen bonding and hydrophobic interaction. These findings highlight the potential application of a new antimicrobial agent against S. aureus in the food industry.